Explanation and Ranking of Auditor Behavioral Indicators Based on Environmental Responsibility - Arab, Leila; sotudeh, Reza; Haghparast, Abbasali; Hirad, Alireza (Business, Marketing, and Finance Open, 2024)
Companies and organizations must be accountable for the environmental impacts of their activities toward future generations. Given the widespread effects of human activities on the environment, including climate change, air and water pollution, and the destruction of ecosystems, companies and organizations bear a significant responsibility for the future of the planet. The objective of this study is to explain and rank the behavioral indicators of auditors based on environmental responsibility. The research method is mixed (qualitative and quantitative) and was conducted in the year 2024. In the qualitative part, interviews were conducted with 15 experts, and theoretical saturation was achieved using grounded theory. In the quantitative part, the Friedman test was used to rank the indicators. Additionally, to validate the indicators, a researcher-designed questionnaire was distributed among 384 university professors and professionals in the field, including faculty members, financial managers, and auditors from the Iranian Court of Audit, using SPSS software. This study identifies 11 components and 39 indicators. The components are as follows: Professional ethics (four indicators), stakeholder consideration (three indicators), environmental standards (three indicators), sustainable development (four indicators), environmental culture (three indicators), evaluation and monitoring (four indicators), sustainability reporting (three indicators), professional competence (five indicators), individual attitudes and values (four indicators), individual responsibility (two indicators), and education and learning (four indicators). Auditors play a key role in identifying the strengths and weaknesses of companies and organizations by assessing their environmental performance. Through thorough examination and transparent reporting, auditors provide a powerful tool for increasing public and stakeholder trust in organizations. This process not only promotes transparency but also helps organizations improve their performance and achieve sustainable environmental goals. This type of assessment, conducted by trained professionals, encompasses various dimensions of environmental impact and provides solutions for improving performance.